Coal reservoir full-aperture pore structure characterization method based on hole connection method
The data correction and connection are carried out through the combined pore method combined with low-temperature carbon dioxide, liquid nitrogen adsorption and mercury impregnation experiments, which solves the error and limitation of small pore structure in the existing technology, and achieves the accuracy of the full pore structure of coal reservoirs. Characterization and multi-scale feature analysis.
Patent Information
- Application Number
- CN202311664441.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-06
- Publication Date
- 2024-12-24
AI Technical Summary
The existing pore structure testing methods have errors and limitations when measuring pore structures less than 100nm, which cannot fully reflect the pore structure characteristics of coal rock, and the results of different methods cannot be used uniformly.
The full pore structure characterization method of coal reservoirs based on the joint pore method was used to obtain data through low-temperature carbon dioxide experiments, low-temperature liquid nitrogen adsorption experiments and mercury injected experiments, and the compression correction and connection pore size were combined to characterize the full pore size of coal reservoirs. Pore structure.
The accuracy of the pore size distribution test results in coal is significantly improved, and the nano-to-micron-scale pore structure characteristics of coal reservoirs are effectively characterized from different scales, with a wide range of applications, simple operation and reliable results.
Smart Images

Figure CN119178706A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coal and coalbed methane mining, and in particular relates to a method for characterizing the full-aperture pore structure of a coal reservoir based on a linked pore method. Background Art
[0002] Mercury intrusion porosimetry is a common pore structure analysis test method. It mainly draws mercury entry and exit curves according to the corresponding mercury volume change under pressure changes, and then calculates the corresponding pore structure characteristic parameters. The test principle is to use external pressure to make mercury overcome surface tension and enter the pores to measure the porosity of the porous medium. This method is fast and accurate in testing samples, and the instrument and equipment test principle is simple. It is currently the most common method for measuring macropore, mesopore pore volume and pore size distribution. However, this method will destroy the pore structure under high pressure (400MPa, corresponding to 3nm), and when excessive external force is applied, it will cause compression of the coal matrix, causing the amount of mercury entry to be greater than the actual pore volume in the coal, resulting in a large error. Therefore, it has limitations in characterizing pore structures less than 100nm.
[0003] Low-temperature liquid nitrogen adsorption is an effective method for characterizing the adsorption pore structure of porous media. The test is carried out based on the principle of physical adsorption and capillary condensation of nitrogen on the solid surface under saturated temperature conditions, and the isothermal adsorption-desorption curves are analyzed to obtain relevant pore data. However, due to the large molecular diameter of nitrogen (0.36nm) and limited instrument accuracy, this technology is difficult to accurately characterize the pore structure with a pore size less than 2nm. The upper limit of the test is about 300nm, which is only suitable for characterizing some micropores and transitional pores. The carbon dioxide adsorption method can enter the pores of 0.3-1.5nm at 273.15K due to the lower molecular diameter (0.33nm) and strong adsorption capacity of CO2, so it has a high accuracy in characterizing pores less than 2nm.
[0004] Therefore, the single pore characterization method is limited by the test principle. The pore ranges of different experimental tests are different. It can only characterize the pore size distribution in a certain range and cannot fully reflect the pore structure characteristics of coal rock. Moreover, due to the different principles and test ranges of different methods, the results cannot be used uniformly. Summary of the invention
[0005] In view of the above technical problems, this application proposes a method for characterizing the full-aperture pore structure of coal reservoirs based on the linked pore method, which aims to effectively combine the data of different test methods to further characterize the full-aperture pore structure characteristics of coal reservoirs. The specific technical solution is as follows:
[0006] A method for characterizing the full-aperture pore structure of a coal reservoir based on a linked pore method, comprising:
[0007] Take the same sample to conduct low-temperature carbon dioxide experiment, low-temperature liquid nitrogen adsorption experiment and mercury injection experiment and obtain experimental data;
[0008] After compressibility correction of mercury injection experimental data, the aperture for connection with low-temperature liquid nitrogen adsorption experimental data was selected;
[0009] Select the aperture for connecting the experimental data of low-temperature carbon dioxide experiment with the experimental data of low-temperature liquid nitrogen adsorption;
[0010] The full-aperture pore structure of the coal reservoir is characterized based on the experimental data of the connected pore size combined with the low-temperature carbon dioxide experiment, the low-temperature liquid nitrogen adsorption experiment data and the compressibility-corrected mercury injection experiment data.
[0011] Furthermore, the method for compressibility correction of mercury injection test data is as follows:
[0012] The mercury injection test data were corrected using the matrix compressibility coefficient, which is Where Kc is the coal matrix compression coefficient, m2 / N; Vc is the original coal matrix volume, cm3 / g; α is the slope of the cumulative mercury injection and pressure curve within the calibration range, unitless; ΔVp is the actual cumulative pore filling volume from the liquid nitrogen adsorption experimental data, cm3 / g; ΔP is the mercury injection pressure increment, MPa;
[0013] Use the following formula to calculate each pressure point P i Pore filling amount:
[0014]
[0015] In the above formula, V Pi and V obs(Pi) The pressure P i Pore filling volume and apparent mercury intrusion under 3 / g,V c(Pi) is the pressure P i Volume of coal matrix below, cm 3 / g; i represents the serial number of the test pressure point; P0 is the starting pressure value of the test.
[0016] Furthermore, the pore size for connecting the experimental data of low-temperature carbon dioxide experiment with that of low-temperature liquid nitrogen adsorption experiment is 2 nm.
[0017] Furthermore, the method for selecting the connection aperture between the compressibility-corrected mercury injection experimental data and the low-temperature liquid nitrogen adsorption experimental data is as follows:
[0018] 1) Plot the relationship between the stage pore volume and pore diameter of the mercury injection test data and the low-temperature liquid nitrogen adsorption test data after compressibility correction;
[0019] 2) The stage pore volume-pore diameter curves of the mercury injection test data and the low-temperature liquid nitrogen adsorption test data after compressibility correction were derived to obtain the curve of the first-order derivative changing with the pore diameter;
[0020] 3) Find the maximum intersection of two first-order derivative curves with the change curve of the aperture in the range of 50-100 nm. The intersection must satisfy (dV / dD)Hg=(dV / dD)N2, and the horizontal coordinate corresponding to the intersection is the connection aperture.
[0021] Furthermore, the method for characterizing the full-aperture pore structure of coal reservoirs based on the combined pore size and low-temperature carbon dioxide experimental data, low-temperature liquid nitrogen adsorption experimental data and compressibility-corrected mercury injection experimental data is as follows:
[0022] 1) The carbon dioxide adsorption data and the low-temperature liquid nitrogen adsorption data are connected at a pore size of 2nm, that is, the pore structure characteristics of the pore size <2nm are characterized by the carbon dioxide adsorption data, and the pore structure of the pore size >2nm is characterized by the low-temperature liquid nitrogen adsorption data;
[0023] 2) The corrected mercury injection data and cryogenic liquid nitrogen adsorption data are spliced at the connecting pore size, that is, the pore structure characteristics of macropores and mesopores are characterized by the corrected mercury injection data, and the transitional pores are characterized by both mercury injection and cryogenic liquid nitrogen;
[0024] 3) The pore structure of coal reservoirs is characterized by the combined corrected mercury injection data, low-temperature liquid nitrogen adsorption data and carbon dioxide adsorption data, and the pore volume and specific surface area distribution characteristics of the full pore size can be obtained.
[0025] The beneficial effects of the present invention are as follows: the characterization method can combine the mercury injection method, the low-temperature liquid nitrogen adsorption method and the carbon dioxide adsorption method to characterize the pore structure of the coal reservoir with full pore size, and after the pores are combined, the accuracy of the pore size distribution test results in the coal can be significantly improved, and the nanometer to micrometer pore structure characteristics of the coal reservoir can be effectively characterized from different scales. The reservoir characterization method has a wide range of applications, is easy to operate, simple to calculate, and has reliable results. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Shown is a flow chart of the characterization method in the embodiment;
[0027] Figure 2 Shown is a stage pore volume curve of the mercury intrusion method test of the raw coal sample in the embodiment;
[0028] Figure 3 What is shown is the stage pore volume curve diagram of the raw coal sample in the embodiment tested by low temperature liquid nitrogen adsorption method;
[0029] Figure 4 Shown is a stage pore volume curve of the raw coal sample carbon dioxide adsorption test in the embodiment;
[0030] Figure 5 What is shown is a comparison diagram of mercury injection data before and after matrix compression effect correction in the embodiment;
[0031] Figure 6 The graph showing the pore size distribution result of the coal sample characterized by the combined carbon dioxide adsorption, low temperature liquid nitrogen adsorption and mercury intrusion method in the embodiment is shown;
[0032] Figure 7 Shown is the nuclear magnetic resonance relaxation T2 spectrum of the raw coal sample in the embodiment. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments.
[0034] Figure 1 What is shown is a flow chart of the characterization method in the embodiment. A method for characterizing the full-aperture pore structure of a coal reservoir based on the linked pore method is described in this embodiment, which specifically includes compressibility correction of mercury injection data, pore size selection by connecting the carbon dioxide adsorption method with the low-temperature liquid nitrogen adsorption method, pore size selection by connecting the low-temperature liquid nitrogen adsorption method with the mercury injection method, and full-aperture splicing joint characterization.
[0035] The characterization steps are as follows:
[0036] 1. Sample collection and processing
[0037] The selection of samples should be representative. After the samples are collected, the coal rock and coal quality of the coal samples are measured according to the "Method for Microscopic Determination of Vitrinite Reflectance of Coal" (GB / T 6948-2008), "Method for Industrial Analysis of Coal" (GB / T 212-2008) and "Method for Microscopic Component Grouping and Mineral Determination of Coal" (GB / T 8899-2013) for vitrinite reflectance, industrial analysis and coal rock microscopic components. At the same time, the same sample is processed and then subjected to low-temperature carbon dioxide experiment, low-temperature liquid nitrogen adsorption experiment and mercury injection experiment.
[0038] 2. Low temperature liquid nitrogen adsorption experiment
[0039] The low-temperature liquid nitrogen adsorption test instruments in this experiment are TriStarII 3020 specific surface and porosity analyzer and Autosorb IQ-MP fully automatic micropore analyzer. The test is carried out according to GB / T21650.2-2008, and the liquid nitrogen adsorption branch data is interpreted based on the multi-point Brunauer-Emmett-Teller (BET) and Barrett-Joyner-Halenda (BJH) models to obtain parameters such as specific surface area, pore volume and pore size distribution in the pore size range of 1-100nm.
[0040] 3. Low temperature carbon dioxide adsorption experiment
[0041] Prepare a powder sample of 60-80 mesh (0.25-0.425 mm) of not less than 250 g for the experiment. This experiment uses the Autosorb IQ-MP fully automatic micropore analyzer to conduct a low-temperature carbon dioxide experiment on the coal sample. After the sample is dried and degassed, it is measured in an ice water bath (273.15K). The CO2 adsorption isotherm is obtained from the relative pressure and adsorption amount. The relative pressure is set to 0.0001-0.03, and the non-local density functional theory (DFT) is used to explain the micropore distribution.
[0042] 4. Mercury Intrusion Test
[0043] The high-pressure mercury injection test was conducted using an AutoPore IV 9500 mercury injection instrument with a maximum working pressure of 227 MPa and a test pore size lower limit of 5.4 nm. The test was conducted in accordance with GB / T 29171-2012. This test method overcomes the capillary force in the coal by continuously increasing the mercury injection pressure, and mercury gradually enters the smaller coal pores from the larger pores, thereby obtaining the pore characteristics of different pore size stages.
[0044] Assuming that the pores in coal are cylindrical capillary models, the pore throat radius is characterized by the Washburn equation:
[0045]
[0046] Where: Rc is the pore throat radius when the mercury injection pressure is Pc, nm; σ is the surface tension, J / m2; θ is the contact angle, °; Pc is the mercury injection pressure, MPa.
[0047] 5. Compressibility Correction of Mercury Intrusion Data
[0048] The high-pressure data (greater than 10 MPa) of the mercury injection method will produce errors due to the matrix compression effect and cannot accurately reflect the actual pore situation. It needs to be corrected by the compression coefficient.
[0049] The matrix compression coefficient Kc is expressed as:
[0050]
[0051] Wherein, Kc is the coal matrix compression coefficient, m2 / N; Vc is the original coal matrix volume, cm3 / g; α is the slope of the cumulative mercury injection amount and pressure curve within the calibration range, unitless; ΔVp is the actual cumulative pore filling amount from the liquid nitrogen adsorption experimental data, cm3 / g; ΔP is the mercury injection pressure increment, MPa.
[0052] Assuming that the coal matrix compression coefficient remains unchanged during the mercury injection process, the volume change of the coal sample matrix is:
[0053]
[0054] Where: Vc(Pi) is the volume of coal matrix under pressure Pi, cm3 / g; i represents the serial number of the test pressure point; P0 is the starting pressure value of the test.
[0055] The pore filling volume at each pressure point Pi is:
[0056]
[0057] Where: VPi and Vobs(Pi) are the pore filling amount and apparent mercury intrusion amount at pressure Pi, cm3 / g.
[0058] Assuming that the pores are all spherical, the change in specific surface area is:
[0059]
[0060] Where: SPi is the change in specific surface area in the ith pressure section, m2 / g.
[0061] VI. Selection of pore size for connecting carbon dioxide adsorption method with low temperature liquid nitrogen adsorption method
[0062] The low-temperature liquid nitrogen adsorption method and the carbon dioxide adsorption method have the same gas adsorption principle, but the experimental conditions and gas characteristics of the two are different. Therefore, there are differences in the pore size range of the test. CO2 gas is an ideal micropore test medium, which can effectively characterize the distribution characteristics of micropores below 2nm, while the low-temperature liquid nitrogen adsorption method has a higher test accuracy for 2 to 100nm. Based on this, the carbon dioxide adsorption data and the low-temperature liquid nitrogen adsorption data are selected to be connected at a pore size of 2nm.
[0063] VII. Selection of pore size for connection between low temperature liquid nitrogen adsorption method and mercury intrusion method
[0064] The testing principle of mercury injection is that as the applied pressure increases, mercury enters the coal pores from large to small; low-temperature liquid nitrogen adsorption condenses in the coal pores from small to large as the applied pressure increases. According to the dominant pore size range of the two testing methods, the pore size range of 50 to 100 nm in the overlapping area of the corrected mercury injection data and low-temperature liquid nitrogen data is selected to meet the requirements of equal volumes of the test media (mercury and liquid nitrogen) required to fill the corresponding pores and smoothly connect the junction points. The junction point here is the connecting pore size.
[0065] The specific method is:
[0066] 1) Draw the relationship between the stage pore volume and pore diameter of the corrected mercury injection and low-temperature liquid nitrogen adsorption;
[0067] 2) respectively taking derivatives of the corrected stage pore volume-pore diameter curves of mercury injection and cryogenic liquid nitrogen to obtain the curves of the first-order derivative versus pore diameter;
[0068] 3) Find the maximum intersection of the two first-order derivative curves within the range of 50 to 100 nm. The intersection must satisfy (dV / dD)Hg=(dV / dD)N2. The horizontal coordinate corresponding to this point is the connection aperture.
[0069] 8. Full-aperture stitching joint characterization
[0070] 1) The carbon dioxide adsorption data and the low-temperature liquid nitrogen adsorption data are connected at a pore size of 2 nm, that is, the pore structure characteristics of the pore size <2 nm are characterized by the carbon dioxide adsorption data, and the pore structure of the pore size >2 nm is characterized by the low-temperature liquid nitrogen adsorption data.
[0071] 2) The corrected mercury injection data and the cryogenic liquid nitrogen adsorption data are spliced at the connecting pore size, that is, the pore structure characteristics of macropores and mesopores are characterized by the corrected mercury injection data, and the transition pores are characterized by both mercury injection and cryogenic liquid nitrogen.
[0072] 3) The pore structure of coal reservoirs is characterized by the combined corrected mercury injection data, low-temperature liquid nitrogen adsorption data and carbon dioxide adsorption data, and the pore volume and specific surface area distribution characteristics of the full pore size can be obtained.
[0073] Example
[0074] Mercury injection experiment, low-temperature liquid nitrogen adsorption experiment and low-temperature carbon dioxide adsorption experiment were carried out on No. 1 coal sample (fat coal) and No. 2 coal sample (gas coal) from the Lianghuai mining area.
[0075] The mercury intrusion porosimetry pore volume curve of the original coal sample is as follows: Figure 2 shown.
[0076] The stage pore volume curve of the original coal sample by low temperature liquid nitrogen adsorption method is as follows Figure 3 shown.
[0077] The pore volume curve of the original coal sample by carbon dioxide adsorption method is as follows: Figure 4 Shown
[0078] 1. Compressibility correction of mercury injection data
[0079] The amount of mercury injected during the mercury injection test is the sum of the amount of mercury filled in the pores, the compression deformation of the matrix, and the shrinkage deformation of the pores not filled with mercury. As the mercury injection pressure increases, the amount of mercury filled in the pores will gradually increase, and the pore deformation will also change accordingly. Therefore, during the mercury injection process, the amount of mercury injected at different mercury injection pressures and the number of pores in the coal, the compression deformation of the coal matrix, and the shrinkage deformation of the pores in the coal are dynamic changes. The relationship between the three is extremely complex, and it is difficult to accurately describe the continuous changes of each variable and the relationship between them. However, the shrinkage deformation of the matrix during the mercury injection process mainly occurs in the pores not filled with mercury, and the pores that have been filled with mercury will not continue to shrink. Therefore, assuming that the compression coefficient of the coal matrix is a constant, and the compression deformation characteristics of the pores not filled with mercury are the same as those of the matrix, the pore increment between adjacent pressure points and the amount of mercury injection have the following relationship:
[0080]
[0081] Wherein, VPi and Vobs(Pi) are the pore filling amount and apparent mercury intrusion amount under pressure Pi, respectively, in cm3 / g; Vc(Pi) is the volume of coal matrix under pressure Pi, in cm3 / g; Kc is the compression coefficient of coal matrix, in m2 / N.
[0082] Assuming that the pores are all spherical, the change in specific surface area is:
[0083]
[0084] Where: SPi is the change in specific surface area in the ith pressure section, m2 / g.
[0085] The corrected pore volume and pore specific surface area can be obtained from the above formula. The results of correcting the matrix compression effect of the test coal sample in the high pressure section are as follows: Figure 5 It is shown that the matrix compression effect of the mercury injection experiment has a significant impact on the test results of micropores and transitional pores. Using the mercury injection method alone to characterize the pore structure will produce a large error.
[0086] 2. Selection of connection aperture
[0087] There are many methods for characterizing the pore structure of reservoirs. However, due to the complex distribution and genesis of nano-micrometer pores in coal reservoirs, this paper selects mercury injection, low-temperature liquid nitrogen adsorption and carbon dioxide adsorption with their respective advantageous pore size segments to jointly characterize the pore structure of coal reservoirs.
[0088] The testing principle of mercury injection is that as the applied pressure increases, mercury enters the pores of the coal body from large to small; low-temperature liquid nitrogen adsorption condenses in the pores of the coal body from small to large as the applied pressure increases. The present invention selects the area (50-100nm) where the two overlap and are their respective advantages, and the volume of the test medium filling the corresponding pore size pores is equal at the junction of the two, that is, the volume of mercury entering the corresponding stage of mercury injection is equal to the adsorption amount of the low-temperature liquid nitrogen adsorption stage, and the connection aperture satisfies the smooth connection of the mercury injection method and the low-temperature liquid nitrogen adsorption method. After mercury injection correction, the first-order derivatives of sample No. 1 and sample No. 2 have intersections at 87nm and 90nm respectively, indicating that the volumes of the two are equal and meet smooth connection. Therefore, the apertures of 87nm and 90nm are used as the connection apertures for the mercury injection method and the low-temperature liquid nitrogen adsorption method for samples No. 1 and No. 2.
[0089] Compared with the mercury injection method, the gas adsorption method has the advantages of avoiding pore damage when measuring the micropore pore structure and being able to test a smaller micropore pore size range. The amount of gas adsorbed in the reservoir is determined by the relative pressure. The isothermal adsorption curve is obtained by measuring the gas filling amount in the reservoir pores under different relative pressures. The pore structure characteristics are obtained by fitting and analyzing the isothermal adsorption curve based on different adsorption models. Compared with low-temperature liquid nitrogen adsorption, carbon dioxide adsorption has the advantages of high analysis temperature, strong energy, and rapid equilibrium, and can test the pore structure characteristics within a smaller pore size range. After comparative analysis, there is an overlapping area in the pore size distribution of carbon dioxide adsorption data and low-temperature liquid nitrogen adsorption data. The pore structure characteristics of pore size <2nm are characterized by carbon dioxide adsorption data, and the pore structure of pore size >2nm is characterized by low-temperature liquid nitrogen adsorption data.
[0090] 3. Full-aperture stitching joint characterization
[0091] Ignoring the differences in the test principles of high-pressure mercury injection, low-temperature liquid nitrogen adsorption and carbon dioxide adsorption experiments, based on the different pore size characterization ranges and accuracies of the three test methods, the optimal pore size segment of each test method was used to conduct a multi-scale comprehensive characterization of the pore characteristics of coals of different ranks. The pore size structure characteristics of micropores (<10nm) were characterized by carbon dioxide adsorption experimental data (<2nm) and part of the low-temperature liquid nitrogen adsorption experimental data (2-10nm), the pore size structure characteristics of transitional pores (10nm-100nm) were characterized by part of the low-temperature liquid nitrogen adsorption experimental data (10nm-100nm), the pore size structure characteristics of mesopores (100nm-1000nm) and macropores (1000nm-10000nm) were characterized by corrected high-pressure mercury injection data (100nm-10000nm), and the pore volume and pore specific surface area information of each pore size segment of each coal sample were statistically analyzed. The results of the joint characterization of coal pore size distribution by carbon dioxide adsorption, low-temperature liquid nitrogen adsorption and mercury injection are shown in the figure. Figure 6 .
[0092] 4. Accuracy Verification
[0093] In order to verify the accuracy of the calibration results, the pore size distribution characteristics of the joint characterization were compared with the results of the nuclear magnetic resonance relaxation method. The nuclear magnetic resonance relaxation T2 spectrum is shown in Figure 7 shown.
[0094] The experimental steps of nuclear magnetic resonance relaxation method are as follows:
[0095] Before the experiment, the coal samples were sieved and crushed to 200 mesh. 5g of coal samples were selected by quartering method, placed in a drying oven at 100℃ for 8h to remove moisture from the coal, and 1-2g of dry coal samples were weighed. The test was conducted using MicroMR12-040V nuclear magnetic resonance analyzer in accordance with SY / T6490-2014.
[0096] The pore size distribution of the joint characterization is highly consistent with the corresponding pore size distribution characterized by nuclear magnetic resonance, which proves the accuracy of the present invention.
Claims
1. A method for characterizing the full-aperture pore structure of a coal reservoir based on the linked pore method, characterized in that: include: Take the same sample to conduct low-temperature carbon dioxide experiment, low-temperature liquid nitrogen adsorption experiment and mercury injection experiment and obtain experimental data; After compressibility correction of mercury injection experimental data, the aperture for connection with low-temperature liquid nitrogen adsorption experimental data was selected; Select the aperture for connecting the experimental data of low-temperature carbon dioxide experiment with the experimental data of low-temperature liquid nitrogen adsorption; The full-aperture pore structure of the coal reservoir is characterized based on the experimental data of the connected pore size combined with the low-temperature carbon dioxide experiment, the low-temperature liquid nitrogen adsorption experiment data and the compressibility-corrected mercury injection experiment data.
2. The method for characterizing the full-aperture pore structure of a coal reservoir based on the linked pore method according to claim 1, characterized in that: The method for compressibility correction of mercury injection test data is: The mercury injection test data were corrected using the matrix compressibility coefficient, which is Where Kc is the coal matrix compression coefficient, m2 / N; Vc is the original coal matrix volume, cm3 / g; α is the slope of the cumulative mercury injection and pressure curve within the calibration range, unitless; ΔVp is the actual cumulative pore filling amount from the liquid nitrogen adsorption experimental data, cm3 / g; ΔP is the mercury injection pressure increment, MPa; Use the following formula to calculate each pressure point P i Pore filling amount: In the above formula, V Pi and V obs(Pi) The pressure P i Pore filling volume and apparent mercury intrusion under 3 / g,V c(Pi) is the pressure P i Volume of coal matrix below, cm 3 / g; i represents the serial number of the test pressure point; P0 is the starting pressure value of the test.
3. The method for characterizing the full-aperture pore structure of a coal reservoir based on the linked pore method according to claim 1, characterized in that: The aperture for connecting the experimental data of low-temperature carbon dioxide experiment with that of low-temperature liquid nitrogen adsorption experiment is 2 nm.
4. The method for characterizing the full-aperture pore structure of a coal reservoir based on the linked pore method according to claim 1, characterized in that: The method for selecting the aperture for connecting the compressibility-corrected mercury injection experimental data with the low-temperature liquid nitrogen adsorption experimental data is: 1) Plot the relationship between the stage pore volume and pore diameter of the mercury injection test data and the low-temperature liquid nitrogen adsorption test data after compressibility correction; 2) The stage pore volume-pore diameter curves of the mercury injection test data and the low-temperature liquid nitrogen adsorption test data after compressibility correction were derived to obtain the curve of the first-order derivative changing with the pore diameter; 3) Find the maximum intersection of two first-order derivative curves with the change curve of the aperture in the range of 50-100 nm. The intersection must satisfy (dV / dD)Hg=(dV / dD)N2, and the horizontal coordinate corresponding to the intersection is the connection aperture.
5. The method for characterizing the full-aperture pore structure of a coal reservoir based on the linked pore method according to claim 1, characterized in that: The method of characterizing the full-aperture pore structure of coal reservoirs based on the experimental data of the combined pore size and low-temperature carbon dioxide experiment, the experimental data of low-temperature liquid nitrogen adsorption and the mercury injection experimental data after compressibility correction is as follows: 1) The carbon dioxide adsorption data and the low-temperature liquid nitrogen adsorption data are connected at a pore size of 2nm, that is, the pore structure characteristics of the pore size <2nm are characterized by the carbon dioxide adsorption data, and the pore structure of the pore size >2nm is characterized by the low-temperature liquid nitrogen adsorption data; 2) The corrected mercury injection data and cryogenic liquid nitrogen adsorption data are spliced at the connecting pore size, that is, the pore structure characteristics of macropores and mesopores are characterized by the corrected mercury injection data, and the transitional pores are characterized by both mercury injection and cryogenic liquid nitrogen; 3) The pore structure of coal reservoirs is characterized by the combined corrected mercury injection data, low-temperature liquid nitrogen adsorption data and carbon dioxide adsorption data, and the pore volume and specific surface area distribution characteristics of the full pore size can be obtained.
Citation Information
Cited By
Performance evaluation method for capturing CO2 by porous carbon material
CN120102402A
Method and system for testing porosity and specific surface area of pre-compressed porous medium
CN121740717A
